Integrasi Spotify dalam Metode Role Playing untuk Meningkatkan Motivasi dan Keterampilan Public Speaking Mahasiswa - Suntoko Suntoko; Rizki Teja Pratama; Achmad Suherman (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
This research is motivated by the low public speaking skills of students, characterized by a lack of courage to speak, fluency in conveying ideas, and low learning motivation in class presentation activities. This condition requires learning actions that provide active, contextual, and interesting speaking experiences. This study aims to improve public speaking skills and student learning motivation through the implementation of the Role Playing method assisted by Spotify. The study used a Classroom Action Research (CAR) design which was carried out in two cycles on class 2C students of the Indonesian Language and Literature Education Study Program at Singaperbangsa University, Karawang, with 30 research subjects. Data collection techniques included speaking skills tests, learning motivation questionnaires, observation, and documentation. The results of the study showed an increase in students' public speaking skills from the initial condition which only got an average score of 57.22, then increased in cycle I with an average of 74.67 and increased in cycle II with an average of 85.00, which was marked by an increase in the average score to exceed the completeness criteria and increased active participation of students in speaking activities. In addition, student learning motivation also increased from the low category to the good category. The study's key findings indicate that the Spotify-assisted role-playing method effectively increased students' speaking confidence and learning engagement. Therefore, the implementation of the Spotify-assisted role-playing method has been proven to significantly improve students' public speaking skills and learning motivation.